If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3(6x-9)=2x-3
We simplify the equation to the form, which is simple to understand
1/3(6x-9)=2x-3
Simplifying:
+ 0.333333333333*(6x-9)=2x-3
Reorder the terms in parentheses
+(+2x-3)=2x-3
Remove unnecessary parentheses
+2x-3=+2x-3
We move all terms containing x to the left and all other terms to the right.
+2x-2x=-3+3
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| 86-3X=42X+16 | | 4.5x+(-5)=17 | | 10(1-2(.5))=-5(2(.5)-1) | | 9-10X=53-24X | | p-5.16=15.48 | | 12(2-x)=4-6(x+2) | | 93+-84= | | 10(1-2(1.5))=-5(2(1.5)-1) | | x-4y=48 | | 3+4y=4a+7 | | 15r+9=96 | | 6p^2+21p= | | 93=-84 | | 7x+3=8x-2 | | r(s+4)+9(s+4)= | | 5z^3+14z^2-24z=0 | | r^4=625 | | 4x-15=4x | | 4x^4-121=0 | | 3(1+6b)+3(6-3b)=21 | | 77-5x=7-9x | | 19x=11x | | 5+6x=25x | | 11x+50=6x+25 | | 2x^3+3x^2-72x-108=0 | | 50C=19N+3 | | 3x=2(x+10) | | 3+n/7=-5 | | 2(0.3r+1)=23-0.1r | | -9+4(x-3)=-4x+3 | | 3(x+3)-sx+7=x+4 | | .04x+.07(12000-x)=720 |